2016
DOI: 10.1002/2015ja022004
|View full text |Cite
|
Sign up to set email alerts
|

Climatological response of Indian low‐latitude ionosphere to geomagnetic storms

Abstract: A climatological response of low‐latitude ionosphere to geomagnetic storms is presented using long‐term global ionospheric maps data from June 1998 to June 2015 covering two solar cycles 23 and 24. The results are presented for daytime forenoon and afternoon sectors under minor, moderate, and major ionospheric storm categories based on minimum Dst index criterion. For the first time the effectiveness of storms is identified using monthly standard deviation as an indicator of the day to day variability in equat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 84 publications
0
14
0
Order By: Relevance
“…Storms from this list along with similar storms from solar cycle 24 have been taken up in the present study. Following the definition of effective ionospheric storms by Suresh and Dashora (2016), storms with minimum Dst between −100 and −200 nT are termed as moderate storms and those with minimum Dst ≤ −200 nT as major storms. Successive storms occurring on consecutive days are analyzed only for the first day (or the MP) and rest of the consecutive stormy events are not analyzed.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Storms from this list along with similar storms from solar cycle 24 have been taken up in the present study. Following the definition of effective ionospheric storms by Suresh and Dashora (2016), storms with minimum Dst between −100 and −200 nT are termed as moderate storms and those with minimum Dst ≤ −200 nT as major storms. Successive storms occurring on consecutive days are analyzed only for the first day (or the MP) and rest of the consecutive stormy events are not analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, a total of 31 geomagnetic latitudes are chosen and corresponding set of geographic coordinates were obtained using quasidipole geomagnetic coordinate calculator (Emmert et al, 2010) which are shown in Figure 1. Quiet time monthly mean GIM VTEC and its corresponding standard deviation for each selected coordinate are computed following Suresh and Dashora (2016). GIM data provide global gridded VTEC values with size of 2.5°× 5°in geographic latitude-longitude for given UT (Jee et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations